PENGGUNAAN SENSOR WATER LEVEL DAN SIRINE ALARM UNTUK MEMBACA KETINGGIAN AIR DENGAN MENGGUNAKAN TEKNOLOGI ARDUINO NANO - Amin, Muhammad; Ananda, Ricki (JURNAL TEKNISI, 2023)
The Silau River is one of the rivers that flows in Asahan. The Silau River flows on the outskirts of the city range which can be seen below the base of the titi, so it is clear that when the rainy season falls it results in a high volume of water, so that flooding can occur and this river continues to flow to the new Silo village, where the village has been 4 times experiencing flooding in four hamlets, where hamlet 1 is the first hamlet the water rises because it is near the coast, then if the water in hamlet 2 has reached 30 to 40 cm, then it is certain that the water in hamlet 1 has reached 1 meter. Therefore floods can occur at any time which can result in material losses and so on. So that researchers are interested in making a design for using water level sensors and sirens to detect water levels, where the working system of this tool will be when hamlet 1 starts to be flooded (sensor 1 designed by the tool has been passed by flood water), then the siren will turn on with a delay time x, so that people in hamlets 2,3 and 4 must be prepared to face flooding to minimize losses caused by flooding and if sensor 2 on the device design is flooded, then it indicates that the water in hamlet one has reached 1 meter, so residents in hamlets 1, 2, 3 and 4 It is mandatory to evacuate to anticipate casualtie